Greeting cards,
Collection of holiday greeting cards. The bulk of the collection are undated, but appear to be from the late 19th century. Cards are for special occasions such as Christmas, New Year's, Valentines Day, Easter and birthday. Some advertising cards are present, but most cards are unsigned and are examples of printing.